Idioms in the Yoki Berampu Songs Lyrics PakPak Boang Language - Dita Aulia Syahrani; Mulyadi Syahputra; Zahria Amalina (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study investigates idiomatic expressions in the song lyrics of Yoki Berampu, a regional singer who uses the Pakpak Boang language. Idioms are essential in communication as they convey meanings that cannot be interpreted literally and reflect cultural values. However, idioms in regional songs are often difficult to understand, especially for those outside the cultural context. This study aims to identify the types of idioms and analyze their meanings. A descriptive qualitative method was employed, with data collected through document analysis of eighteen selected song lyrics. The findings reveal 39 idiomatic expressions, consisting of 7 pure idioms, 12 semi-idioms, and 20 literal idioms. Each type demonstrates different levels of semantic transparency, where pure idioms are highly abstract, semi-idioms relate to sensory experiences, and literal idioms convey meanings more transparently. These expressions are used to represent emotions, social values, and cultural identity. The study implies that idiomatic expressions in regional songs function not only as linguistic elements but also as a medium for preserving cultural identity and conveying complex meanings.